The Influence of Chip Size Variation in the Pulping Process from Jabon Wood - Dirna, Fitria Cita; Wahyuningtyas, Irma (Indonesian Journal of Chemical Research, 2025)
Wood is the primary raw material in the pulp and paper industry. Due to its favorable fiber characteristics, Jabon wood (Anthocephalus cadamba Miq.) is a promising fast-growing pulp and paper production species. This study investigates the effect of nine different chip size variations, including their length and thickness (1×3, 3×3, 5×3, 1×5, 3×5, 5×5, 1×7, 3×7, and 5×7), on pulp yield, fiber properties, and chemical performance using the kraft pulping method. Parameters measured include pulp yield, fiber length, fiber diameter, lumen diameter, cell wall thickness, and derived indices such as Runkle ratio, felting power, Muhlsteph ratio, rigidity coefficient, flexibility ratio, and kappa number. Results show that chip size does not significantly affect yield but influences fiber quality and kappa number. Shorter and thinner chips improved chemical penetration, resulting in lower kappa numbers and higher-quality pulp. Fiber classification based on IAWA criteria placed jabon wood in class II, indicating medium to suitable suitability for pulp. The study provides novel insight into optimizing chip geometry for kraft pulping of jabon wood, which has rarely been explored in previous literature. These findings are relevant for enhancing raw material efficiency and pulp quality in industrial applications.